Food, faith, social service and institution building: the Annamrita programme of the Hare Krishna movement in India. Issue 1 (2nd January 2017) - Pandya, Samta P.
ABSTRACT: Based on fieldwork with the Annamrita programme, a food-based social service of ISKCON or the Hare Krishna movement in India, I look at the intricate connection between food, faith, social service and institution building. Formally known as the ISKCON Food Relief Foundation, the Annamrita programme has partnered with the government's midday meal scheme for school children. From the point of view of sociology of food and sociology of religion, I propose that food is a cultural, moral and emotional investment for ISKCON. I describe how a faith-based social service through the instrument of food becomes a mode of bridging and institution building. The governmentality of this food service and the sacred public–private partnership is a specific kind of cultural and macroeconomic intervention in a resource-limited setting such as India. Camouflaged and embedded in this programme is an element of cultural hegemony and a Krishna consciousness-governed nationalism, with the ideas of the nation as a sacred land. Krishna is considered as the vanguard of sacralisation and the faith messages of ISKCON inevitably accompany the service package.